العوامل الاجتماعية والاقتصادية المؤثرة في ارتكاب الجريمة دراسة ميدانية في سجون محافظة اللاذقية - العشعوش أيمن; حليوة أيمن (Latakia University Journal - Economic and Legal Sciences Series, 2016)
The research aims to study the social and economic factors affecting the occurrence of crime through a field study on a sample of convicts in the prisons of the province of Latakia. Find adopted a descriptive analytical method, where the questionnaire was designed and distributed to (118) of the governed, and using statistical methods was reached following results: 1- The social factors that affect the occurrence of the crime in order of degree of impact: the disintegration of family relationships, lack of role of the father, the psychological insecurity within the family, not to adapt to the family, satellite channels, the weakness of religious faith, Comrade rotten in the school or neighborhood, violence inside family, leisure time, the absence of values and social norms in the family, alcohol and drugs, failure in school, emotional relationship between parents and children disorder, ignorance of the right to education for the children, friction different cultural and social values. 2- The economic factors that affect the affect of the crime in order of degree of impact: lack of access to basic needs, inequality in spending, the cost of living, unemployment, family budget deficit, lack of livelihood project, the family’s poverty, high expense without responsibility, increase the family burden, weak household income. 3- crime among young singles with low education classes are spread, and the unemployed, and living in the city within the slums. يهدف البحث إلى دراسة العوامل الاجتماعية والاقتصادية المؤثرة في وقوع الجريمة من خلال دراسة ميدانية على عينة من المحكومين في سجون محافظة اللاذقية. اعتمد البحث على المنهج الوصفي التحليلي, و تمّ تصميم استبانة وتوزيعها على (118) من المحكومين, وباستخدام الأساليب الإحصائية تمّ التوصل إلى النتائج الآتية: 1- إنّ العوامل الاجتماعية التي تؤثر في وقوع الجريمة مرتبة حسب درجة تأثيرها: تفكك العلاقات الأسرية, افتقاد دور الأب, فقدان الأمن النفسي داخل الأسرة, عدم التكيف مع الأسرة, القنوات الفضائية, ضعف الوازع الديني, الرفيق الفاسد في المدرسة أو الحي, العنف داخل الأسرة, وقت الفراغ, غياب القيم والمعايير الاجتماعية في الأسرة, المسكرات والمخدرات, الإخفاق في المدرسة, اضطراب العلاقة الوجدانية بين الوالدين والأبناء, الجهل بالتربية الصحيحة للأبناء, الاحتكاك بقيم ثقافية واجتماعية مختلفة. 2- إنّ العوامل الاقتصادية التي تؤثر في وقوع الجريمة مرتبة حسب درجة تأثيرها: عدم الحصول على الاحتياجات الأساسية, والتفاوت الطبقي في الإنفاق, غلاء المعيشة, والبطالة, وعجز ميزانية الأسرة, وانعدام سبل العيش المشروع, وفقر الأسرة, والمصروف المرتفع من دون مسؤولية, وزيادة أعباء الأسرة,و ضعف دخل الأسرة. 3- تنتشر الجريمة بين صفوف الشباب العزاب من ذوي التعليم المنخفض, والعاطلين عن العمل, والقاطنين في المدينة ضمن الأحياء العشوائية.